A new kaonic helium measurement in gas by SIDDHARTINO at the DAΦNE collider*This article is dedicated to the memory of a colleague and friend George Beer, with whom some of us shared the adventure of strangeness physics for many years. (1st May 2022) - Sirghi, D; Sirghi, F; Sgaramella, F; Bazzi, M; Bosnar, D; Bragadireanu, M; Carminati, M; Cargnelli, M; Clozza, A; Deda, G; De Paolis, L; Del Grande, R; et al.
Abstract: The SIDDHARTINO experiment at the DAΦNE collider of INFN-LNF, the pilot run for the SIDDHARTA-2 experiment which aims to perform the measurement of kaonic deuterium transitions to the fundamental level, has successfully been concluded in July 2021. The paper reports the main results of this run, including the optimization of various components of the apparatus, among which the degrader needed to maximize the fraction of kaons stopped inside the target, through measurements of kaonic helium transitions to the 2p level. The obtained shift and width values are ε 2p = E exp − E e.m = 0.2 ± 2.5(stat) ± 2.0(syst) eV and Γ2p = 8 ± 10 eV (stat), respectively. This new measurement of the shift, in particular, represents the most precise one for a gaseous target and is expected to contribute to a better understanding of the kaon–nuclei interaction at low energy. The results obtained in this pilot run, combined with the foreseen additional veto systems and projected for the total 48 SDD arrays of the SIDDHARTA-2 final setup, represent a solid starting point for the successful measurement of the kaonic deuterium 2p → 1s transition, main goal of the experiment.